PENGARUH PERLAKUAN ASAM TUNGGAL DAN BERURUTAN PADA LIGNIT DAN DAYA SERAPNYA PADA ARSENIT - Damris Muhammad, ; Abu Bakar, (Matematika dan Sains, 2010)
The three lignite samples with difference mineral content were treated using single acid of HCl and successively with HCl and H2SO4. The active carbon produced was treated by heating at 900°C. Reaction isoterm of adsorbent resulted was tested to arsenite. Degree of demineralisation of lignite based on the kind of acid and demineralisation step done. The high of demineralisation degree will give the high adsord to active carbon resulted. 2SO4. The active carbon produced was treated by heating at 900°C. Reaction isoterm of adsorbent resulted was tested to arsenite. Degree of demineralisation of lignite based on the kind of acid and demineralisation step done. The high of demineralisation degree will give the high adsord to active carbon resulted.